Bioaccessibility and Antioxidant Capacity of Bioactive Compounds From Various Typologies of Canned Tomatoes - Izzo, Luana; Castaldo, Luigi; Lombardi, Sonia; Gaspari, Anna; Grosso, Michela; Ritieni, Alberto (Frontiers in Nutrition, 2022)
Tomato (Solanum lycopersicum L.) is one of the most consumed vegetables in the world which contains high amounts of antioxidants phytochemicals and essential nutrients. Although is commonly consumed as fresh, more than 80% of their consumption derives from processed products. Since limited information on the changes in the bioaccessibility of bioactive compounds during the gastrointestinal digestion was reported, this current study aimed to monitor the antioxidant activity, total polyphenolic, carotenoid content, and their bioaccessibility during an in vitro gastrointestinal digestion of different typologies (n=7) of canned tomato. A comprehensive evaluation of the polyphenolic profile of digested and not digested samples was ascertained through ultra-high-performance liquid chromatography combined with a high-resolution Orbitrap mass spectrometry. Results highlighted a considerable content of rutin (1.191-7.905 mg/100g), naringenin (0.359-1.452 mg/100g), chlorogenic acid (1.857-11.236 mg/100g) and lycopene (50.894-222.061 mg/kg) in the analyzed matrices. After in vitro gastrointestinal digestion, a large variability, losses and low recovery were recorded. An appreciable percentage of rutin (30.7%), naringenin (29.6%), chlorogenic acid (25.8%) and lycopene (varied between 9.3-20.0%) remain bioaccessible after the in vitro gastrointestinal digestion. Our study could be a valid support to evaluate which content of bioactive compounds may be real bioaccessible to exercise beneficial effects to human health.